KEANEKARAGAMAN DAN STRUKTUR VEGETASI MANGROVE DI PANTAI BAMA – DERMAGA LAMA TAMAN NASIONAL BALURAN JAWA TIMUR - Putrisari Putrisari; Suhartini Suhartini; Ratnawati Ratnawati (Kingdom (The Journal of Biological Studies), 2017)
This research is about diversity and vegetation structure of mangrove in Bama until Dermaga Lama shores, Baluran National Park, East Java wich is conducted for for three weeks. This research aims to find out of species diversity, distribution patterns species and zoning types of mangrove plants.               This is an explorative research, with research object is mangroves, using purpose sampling with terraced strip method. Location in this research divided being two stations, respectively covering an area of 4 ha and 9 ha.               Results of this research evidence that Station 1 there were two mayor mangrove (Rhizophora stylosa and R. apiculata), three minor mangrove (Xylocarpus granatum, Heritiera littoralis and Excoecaria agallocha) And eight mangrove associates (Corypha utan, Syzygium polyanthum, Terminalia catappa, Ardisia sp, Desmodium umbellatum, Caesalpinia sp, Clerodendrum sp and Buchanannia arborescens). Station 2 there were six mayor mangrove (R. apiculata, B. gymnorrhiza, C. tagal, S. caseolaris and S. alba), four mangrove minor (H. littoralis, E. agallocha, sea spikes and A. speciosum), dan 10 mangrove associates (C. utan, S. polyanthum, T. catappa, B. arborescens, Calophyllum inophyllum, Pongamia pinnata, D. umbellatum, Clerodendrum sp, Scaevola taccada and Ardisia sp). Diversity in both stations, category trees, poles and seedlings is moderate (1 H 3), for sapling category, station 1 havelow category (H '1), and station 2 has moderate category. Evenness index in  trees categories on both stations are low (0.3 E 0.6). Category pole, sapling and seedling has high evenness index (E 0.6). Index of species richness in the category tree, trees, saplings and seedlings at the two stations is low (R 3.5). Distribution pattern at both stations R. apiculata stand for pole category is uniform. R. apiculata stands for tree category at the station two is uniform. The rest all clustered category.Station 1 has three zones namely seaward zone, middle zone and the landward zone. Station 2 has four zones, namely, the seaward zone, middle zone, the landward zone, and transects 1, 2, 4 dam 5, has a zone of S. caseolaris mixed with R. apiculata (overlap).Keywords: Mangrove, distribution patterns and Zoning.